Hospital health literacy conceptual explanation: A qualitative content analysis based on experts and population perspectives - Fatemeh Bahrambeygi; Sakineh Rakhshanderou; Ali Ramezankhani; Mohtasham Ghaffari (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND AND AIM: Given the complexities of the health care system and the importance of the subject and effects of health literacy in all aspects of care, defining specific health literacy in this context seems necessary. The purpose of this research was to explain the concept of hospital health literacy (HHL), its definition, and the related dimensions using the qualitative research method. MATERIALS AND METHODS: An exploratory qualitative design was used. Exploratory, open-ended, and face-to-face interviews based on the interview guide were used to elicit participants' perspectives between July 2021 and January 2022. By using the content analysis method, researchers coded transcripts and collated these codes into sub-categories and then merged them into the main category and explored the dimensions of the concept. RESULTS: A total of 23 service providers and 25 service recipients were included in the study. Analysis of qualitative data led to the identification of 6 categories and 25 sub-categories including cognitive literacy, functional (basic) literacy, communicative literacy, behavioral literacy, media literacy, and emotional literacy. CONCLUSION: The findings of the present study provide a deep understanding of the concept of HHL that could be applied to develop valid and reliable measurement tools for assessing HHL among a variety of populations. Also, it is hoped that the present attempt can be useful to guide future research and interventions as well as to provide a clear base for planning, implementing, and evaluating interventions aimed at promoting individuals' health literacy in health settings.